Out of the Ashes : Learning Lessons from the Past to Guide Education Recovery in Liberia - World Bank (Washington, DC, 2017)
This Country Status Report (CSR) for Liberia is part of an ongoing series of country specific reports being prepared by the World Bank in collaboration with governments and development partners. The series aims to enhance the knowledge base for policy development. This report is intended to help engage a diverse audience on issues and policies in the education sector and to develop a shared vision for the future of Liberia. It is the first sector-wide report produced on the education system in Liberia since the end of the war. A policy options matrix follows the executive summary, which will provide government and partners with guidance on the key priorities to tackle. Besides consolidating information in a policy-relevant manner, this CSR makes a unique contribution to the education knowledge base by documenting not only traditional and basic indicators, such as gross enrollment rates and retention, but also examining the performance of the education system in terms of access, quality, equity, and resource allocation and utilization. The report also includes chapters on education governance and teacher management. This report highlights the country's significant education progress since the end of the 14-year civil war in 2003 and the challenges that need to be addressed.